G97(P) Delivering multi-disciplinary ethics & law training in a specialist children's hospital – current knowledge and attitudes. (24th May 2017) - Griffiths, B; Tobin, H; Sharma, S; Brierley, J
Abstract : Introduction: Medical ethics forms part of the medical undergraduate curriculum in the UK, however there is little structure for most postgraduates. Unsurprisingly paediatric trainees report that they do not feel confident in their understanding of ethical principles and the law. 1 We explored the level of ethics training and knowledge in medical and allied health professionals (AHP) in a specialist children's hospital attending an open 7 week program of ethics seminars. We report findings of a survey exploring training and attitudes in medical ethics, and describe the lecture series. Method: Delegates responded to a series of questions at each session using interactive software (Turning Point). Results: The largest group attending were doctors but at least 50% were AHPs. Conclusion: The results presented are consistent with the literature with 71% of delegates reporting a lack of confidence in medical ethics. 2 We have delivered a comprehensive education program that received excellent feedback and believe that there is demand for increased ethics teaching in postgraduate training across professions.